Health Disparities among adults cared for at an urban cystic fibrosis program - Emily DiMango (Orphanet Journal of Rare Diseases, 2021)
Abstract Background Evidence is conflicting regarding differential health outcomes in racial and ethnic minorities with cystic fibrosis (CF), a rare genetic disease affecting approximately 28,000 Americans. We performed a cross-sectional analysis of health outcomes in Black/Latinx patients compared with non-Hispanic Caucasian patients cared for in a CF center in New York City. Adult patients enrolled in the CF Foundation Patient Registry at the Columbia University Adult CF Program and seen at least once during 2019 were included. Health metrics were compared between Black/Latinx and non-Hispanic Caucasian patients. Results 262 patients were eligible. 39 patients (15%) identified as Black/Latinx or non-Hispanic Caucasian. Descriptive statistics are reported with mean (standard deviation). Current age was 35.9 (13.3) years for non-Hispanic Caucasian and 32.0 (9.3) years for Black/Latinx patients (p = 0.087). Age of diagnosis did not differ between groups; 9.56 (15.96) years versus 11.59 (15.8) years for non-Hispanic Caucasian versus Black/Latinx respectively (p = 0.464). Pulmonary function, measured as mean forced expiratory volume in one second (FEV1) was 70.6 (22.5) percent predicted in non-Hispanic Caucasian versus 59.50 (27.9) percent predicted in Black/Latinx patients (p = 0.010). Number of visits to the CF clinic were similar between groups. When controlled for age, gender, co-morbidities, median income, and insurance status, there was a continued association between minority status and lower FEV1. Conclusions Minorities with CF have significantly lower pulmonary function, the major marker of survival, than non-Hispanic Caucasians, even when controlled for a variety of demographic and socioeconomic factors that are known to affect health status in CF. Significant health disparities based on race and ethnicity exist at a single CF center in New York City, despite apparent similarities in access to guideline based care at an accredited CF Center. This data confirms the importance of design of culturally appropriate preventative and management strategies to better understand how to direct interventions to this vulnerable population with a rare disease.